HUBUNGAN PENGETAHUAN DAN MOTIVASI IBU TERHADAP PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS PAAL MERAH II KOTA JAMBI TAHUN 2026 - Sunarti Lubis; Nurul Fatmah; Lusi Afriyani; Deliana Br Karo (LPPM STIKes Mitra Adiguna, 2026)
Newborn mortality is a leading cause of child death, particularly in the first week after birth when their immune systems are still weak. Late initiation of breastfeeding has been shown to improve child health and reduce infant mortality and disease rates. Exclusive breastfeeding can protect against life-threatening diseases, boost the baby's immune system, and support physical growth and brain development. This study aims to determine the relationship between maternal knowledge and motivation and exclusive breastfeeding at the Paal Merah II Community Health Center in Jambi City. The method used in this study was quantitative, with an analytical survey design using a cross-sectional approach. Data were collected through questionnaires and analyzed using univariate analysis to describe variables, and bivariate analysis using the Chi-Square test to examine the relationship between variables. The sample consisted of 52 respondents drawn using a total sampling technique.The results of the Chi-Square statistical test showed a significant relationship between knowledge and exclusive breastfeeding (p-value 0.006), while no significant relationship was found between motivation and exclusive breastfeeding (p-value 0.131). The conclusion of this study indicates a relationship between maternal knowledge and the implementation of exclusive breastfeeding. However, there was no relationship between maternal motivation and exclusive breastfeeding. Continuous education and motivation by health workers are essential to improve the achievement of exclusive breastfeeding in the Paal Merah II Community Health Center (Puskesmas) work area in Jambi City.